2018
DOI: 10.2147/ott.s178131
|View full text |Cite
|
Sign up to set email alerts
|

Low expression level of ASK1-interacting protein-1 correlated with tumor angiogenesis and poor survival in patients with esophageal squamous cell cancer

Abstract: ObjectiveTo investigate the expression of tumor suppressor protein ASK1-interacting protein-1 (AIP1) in human esophageal squamous cell carcinoma (ESCC) and its role in tumor progression, angiogenesis, and prognosis.MethodsA total of 117 biopsy samples were obtained from ESCC patients. None of the patients had distant metastasis before surgery, and did not receive preoperative chemotherapy or radiotherapy. Immunohistochemistry was used to detect the expression of AIP1 protein and vascular endothelial growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Sections were treated with the Envision + DAB kit (Dako, Glostrup, Denmark), according to the manufacturer’s instructions. A semi-quantitative blind method previously described was used to measure the staining intensity and the proportion of positive cells ( Sun et al, 2018 ). Ten visual fields were observed at 400X magnification.…”
Section: Methodsmentioning
confidence: 99%
“…Sections were treated with the Envision + DAB kit (Dako, Glostrup, Denmark), according to the manufacturer’s instructions. A semi-quantitative blind method previously described was used to measure the staining intensity and the proportion of positive cells ( Sun et al, 2018 ). Ten visual fields were observed at 400X magnification.…”
Section: Methodsmentioning
confidence: 99%
“…VEGF may have an important role in tumor progression and metastatic spreading as well as in cancer angiogenesis [ 4 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. One of the regulators of VEGF-A is the NFE2L3 nuclear transcription factor which is associated with a poor prognosis in pancreatic cancer.…”
Section: Influence Of Vegf On Tumor Growth and Vascularizationmentioning
confidence: 99%
“…None of the patients had distant metastases before surgery, and they did not undergo preoperative chemotherapy or radiotherapy. Patients with a high expression of VEGFR-2 and a high level of tumor vascularization were characterized by a lower five-year survival rate ( p < 0.05) [ 24 ]. About 70% of the 408 examined BC patients had high VEGF-C expression which was strongly associated with severe tumor stages ( p = 0.019), significant Ki67 proliferation index, LN metastases (N3) and lymphatic vascular invasion in univariate analysis [ 4 ].…”
Section: Influence Of Vegf On Tumor Growth and Vascularizationmentioning
confidence: 99%
“…Particularly, downregulation of DAB2IP expression was reported to be associated with resistance to chemo or radio therapy and worse outcome in several types of human cancers [ 6 , 11 16 ]. Additionally, Sun et al reported that decreased expression of DAB2IP correlated with ESCC progression and poor prognosis in surgically resected samples [ 17 ]. To date, however, the molecular status of the DAB2IP gene in ESCC patients treated with definitive chemoradiotherapy and the relationship between the expression of DAB2IP and chemoradiosensitivity in ESCC has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%